Analisis Perceived Employ ability Lulusan di Bisnis Digital Universitas Padjadjaran - Nurmahrini, Amara; Sondari, Mery Citra (LPPM Universitas dr. Soebandi, 2023)
The evolution of industrial automation is changing the view of employability of graduate groups, so it is important for universities to provide programs that help their graduates become more competent when entering the workforce. Therefore, a study was conducted to analyze the perception of employability of a group of graduates of the Padjadjaran University Digital Business Study Program. This research involved 100 participants from convenience sampling through filling out questionnaires. The sample was then analyzed using the hierarchical regression method to understand how personal, professional, and contextual factors can influence employability perceptions. The results showed that the three factors had a positive and significant influence on increasing the perceived employability of the Digital Business graduates group of Universitas Padjadjaran, where the three factors together explained 52.4% of the perceived employability of this group. So, the study program can use the results of this study to make relevant evaluations and improvements.